Julieta Zarco Treinta años de cine, política y memoria en la Argentina (Altre Modernità, 2016)
Julieta Zarco Treinta años de cine, política y memoria en la Argentina (Buenos Aires, Editorial Biblos, 2016, 174 pp., ISBN: 978-987691403-1)di Flavio Fiorani